2023
DOI: 10.1108/bepam-10-2022-0153
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability risk assessment in mega construction projects

Cansu Coskun,
Irem Dikmen,
M. Talat Birgonul

Abstract: PurposeMegaprojects are large-scale and long-term investments. Three pillars of sustainable construction objectives, namely, social, environmental and economic, should be integrated into megaproject risk management to ensure long-term success. A risk assessment method, Risk Assessment Method for Sustainable Construction Objectives in Megaprojects (RAMSCOM), was developed for this purpose.Design/methodology/approachRAMSCOM was developed based on the latest concepts and identifying relevant and critical sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Several studies have recognized the value of quantitative risk assessment models in providing a structured and numerical framework for analyzing specific risk factors associated with mega infrastructure projects [8]. Quantitative models often involve probabilistic analyses, simulation techniques, and mathematical modeling to assess risks related to costs, scheduling, and technical complexities.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have recognized the value of quantitative risk assessment models in providing a structured and numerical framework for analyzing specific risk factors associated with mega infrastructure projects [8]. Quantitative models often involve probabilistic analyses, simulation techniques, and mathematical modeling to assess risks related to costs, scheduling, and technical complexities.…”
Section: Related Workmentioning
confidence: 99%
“…These methods were applied to 11 megaconstruction projects for risk assessment and the results showed that it can assist practitioners to develop better risk management plans. Likewise, Coskun et al (2023) developed a risk assessment method, namely Risk Assessment Method for Sustainable Construction Objectives in Megaprojects (RAMSCOM), for sustainable risk assessment of mega construction projects. This method utilizes the hierarchical analysis method (AHP) and cross impact analysis (CIA) to identify and quantify threats related to the importance of the sustainability objectives, and its effectiveness was validated on a major project.…”
Section: Related Studiesmentioning
confidence: 99%